2019
DOI: 10.7717/peerj.6143
|View full text |Cite
|
Sign up to set email alerts
|

Efficient generation of human primordial germ cell-like cells from pluripotent stem cells in a methylcellulose-based 3D system at large scale

Abstract: BackgroundThe mechanisms underlying human germ cell development and infertility remain largely unknown due to bioethical issues and the shortage of experimental materials. Therefore, an effective in vitro induction system of human primordial germ-like cells (hPGCLCs) from human pluripotent stem cells (hPSC) is in high demand. The current strategies used for the generation of hPGCLCs are not only costly but also difficult to perform at a large scale, thereby posing barriers to further research. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…Gametogenesis has been thoroughly studied in model organisms, and in some aspects, in vitro differentiation systems using embryonic stem (ES) cells [5,6] and induced pluripotent stem (iPS) cells [7,8]. By now, a lot of information has been gathered about the epigenetic regulation, the specific transcription factors, important signalization events, and key effectors necessary for commitment of stem cells to germline fate [9,10,11,12,13,14] from different model organism and by in vitro differentiation of stem cells to primordial germ-cell-like cells (PGCLCs) [9,10,11,12,13,14,15,16,17].…”
Section: Introduction: Germline Soma and Embryonic Stem Cellsmentioning
confidence: 99%
“…Gametogenesis has been thoroughly studied in model organisms, and in some aspects, in vitro differentiation systems using embryonic stem (ES) cells [5,6] and induced pluripotent stem (iPS) cells [7,8]. By now, a lot of information has been gathered about the epigenetic regulation, the specific transcription factors, important signalization events, and key effectors necessary for commitment of stem cells to germline fate [9,10,11,12,13,14] from different model organism and by in vitro differentiation of stem cells to primordial germ-cell-like cells (PGCLCs) [9,10,11,12,13,14,15,16,17].…”
Section: Introduction: Germline Soma and Embryonic Stem Cellsmentioning
confidence: 99%
“…Different stages correspond to distinct gene expressions and epigenetic regulations [ 26 ]. These distinct epigenetic regulatory networks of female GCs at sequential developmental phases could be studied through the genome-wide DNA methylation and chromatin accessibility using single-cell resolution [ 88 ]. These efforts on female GCs development mechanisms would contribute to a more efficient and stable female GC induction in vitro .…”
Section: Current Challenges and Future Perspectivesmentioning
confidence: 99%
“…Although human PGCLCs had been recapitulated in vitro , U-bottom 96 plates or other similar plates used in these studies limited the scale production of human PGCLCs production [ 6 8 ]. Recently, a new modified system of methylcellulose-based 3D induction system combined with low-cell attachment plates was reported to produce human PGCLCs from human PSCs at a large scale, with similar gene expression and epigenetic modification profiles to human PGCs [ 88 ]. Besides the 3D induction system, 3D bioprosthetic ovaries were also confirmed to provide 3D support for oocyte cultivation.…”
Section: Current Challenges and Future Perspectivesmentioning
confidence: 99%
“…These PGCs can either be auto-transplanted into the testes (in vivo) or used in vitro in order to induce the development of gametes [113][114][115][116]. Recently, iPSCs were developed from Klinefelter and NOA patients [117,118]. It was shown that iPSC from rodents, monkeys, and humans can be differentiated into male germ cells [4,85,112,[118][119][120][121][122][123][124][125][126][127][128].…”
Section: Induced Pluripotent Stem Cellsmentioning
confidence: 99%
“…Recently, iPSCs were developed from Klinefelter and NOA patients [117,118]. It was shown that iPSC from rodents, monkeys, and humans can be differentiated into male germ cells [4,85,112,[118][119][120][121][122][123][124][125][126][127][128]. The addition of bone morphogenetic proteins (BMPs) to human iPSC induced their differentiation into primordial germ and meiotic cells [129].…”
Section: Induced Pluripotent Stem Cellsmentioning
confidence: 99%